Prolonged Survival Following Pig‐to‐Primate Liver Xenotransplantation Utilizing Exogenous Coagulation Factors and Costimulation Blockade. Issue 8 (6th June 2017) - Shah, J. A.; Patel, M. S.; Elias, N.; Navarro‐Alvarez, N.; Rosales, I.; Wilkinson, R. A.; Louras, N. J.; Hertl, M.; Fishman, J. A.; Colvin, R. B.; Cosimi, A. B.; Markmann, J. F.; et al.
Abstract : Since the first attempt of pig‐to‐primate liver xenotransplantation (LXT) in 1968, survival has been limited. We evaluated a model utilizing α‐1, 3‐galactosyltransferase knockout donors, continuous posttransplant infusion of human prothrombin concentrate complex, and immunosuppression including anti–thymocyte globulin, FK‐506, methylprednisone, and costimulation blockade (belatacept, n = 3 or anti‐CD40 mAb, n = 1) to extend survival. Baboon 1 remained well until postoperative day (POD) 25, when euthanasia was required because of cholestasis and plantar ulcers. Baboon 2 was euthanized following a seizure on POD 5, despite normal liver function tests (LFTs) and no apparent pathology. Baboon 3 demonstrated initial stable liver function but was euthanized on POD 8 because of worsening LFTs. Pathology revealed C4d positivity, extensive hemorrhagic necrosis, and a focal cytomegalovirus inclusion. Baboon 4 was clinically well with stable LFTs until POD29, when euthanasia was again necessitated by plantar ulcerations and rising LFTs. Final pathology was C4d negative and without evidence of rejection, inflammation, or thrombotic microangiopathy. Thus, nearly 1‐mo rejection‐free survival has been achieved following LXT in two of four consecutive recipients, demonstrating that the porcine liver can support life in primates for several weeks and has encouraging potential for clinical application as a bridge to allotransplantation for patients with acute‐on‐chronic or fulminant hepatic failure. Abstract : The addition of costimulation blockade, in conjunction with exogenous coagulation factors, prolongs survival following pig‐to‐primate liver xenotransplantation, achieving the longest survivals reported to date.